2020
DOI: 10.48550/arxiv.2006.10764
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence for supernova feedback sustaining gas turbulence in nearby star-forming galaxies

Cecilia Bacchini,
Filippo Fraternali,
Giuliano Iorio
et al.

Abstract: It is well known that gas in galaxy discs is highly turbulent, but there is much debate on which mechanism can energetically maintain this turbulence. Among the possible candidates, supernova (SN) explosions are likely the primary drivers but doubts remain on whether they can be sufficient in regions of moderate star formation activity, in particular in the outer parts of discs. Thus, a number of alternative mechanisms have been proposed. In this paper, we measure the SN efficiency η, namely the fraction of th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 86 publications
(151 reference statements)
2
17
0
Order By: Relevance
“…The curves in the KED plot show fitted relationships between the KED generated by supernovae and the Σ SFR for the indicated efficiencies of converting SN energy into turbulence, and for galaxy scale heights of 850 pc and 540 pc. These theoretical KEDs come from equation 3.7 in Bacchini et al (2020), which is…”
Section: Pixel-pixel Scatter Plotsmentioning
confidence: 99%
See 4 more Smart Citations
“…The curves in the KED plot show fitted relationships between the KED generated by supernovae and the Σ SFR for the indicated efficiencies of converting SN energy into turbulence, and for galaxy scale heights of 850 pc and 540 pc. These theoretical KEDs come from equation 3.7 in Bacchini et al (2020), which is…”
Section: Pixel-pixel Scatter Plotsmentioning
confidence: 99%
“…where η is the efficiency of energy conversion from supernova to turbulence, f cc = 1.3 × 10 −2 M −1 is the number of core-collapse supernovae per solar mass of stars, E SN = 10 51 erg is the supernova energy, H is the disk thickness and v turb is the turbulent gas velocity dispersion (the ratio of these latter two quantities gives the turbulent dissipation time). Bacchini et al (2020) compare the radial profiles of turbulent energies in 10 nearby galaxies with the SFRs and derive an average efficiency of 1.5 1.8 0.8 % if all of the turbulence comes from star formation. Because the required efficiency is relatively low, they concluded that supernovae related to star formation can drive most of the interstellar turbulence.…”
Section: Pixel-pixel Scatter Plotsmentioning
confidence: 99%
See 3 more Smart Citations